STRATEGI DESAIN BERKELANJUTAN PADA BANGUNAN HOTEL BERBASIS KONSEP GREEN HOTEL - Pebriyanti, Ni Luh Putu Eka (Jurnal Arsitektur Komposisi, 2017)
Abstract: Application of the concept of sustainable development requires integration between the micro scale (building), meso scale (building group) and macro scale (city). Since 2008, ASEAN has rewarded hotels in the world that meet environmentally sound hotel standards. The Ministry of Tourism and Creative Economy has appreciated and organized the award of the National Green Hotel Award since 2011. This research focuses on identifying and analyzing sustainable design strategies at three hotels in Jakarta and Bali covering efficiency, conservation and management of various elements: land, energy , water, materials, air and indoor health, and environmental management. The analysis used normative architectural criticism approach on the standard study in designing hotel buildings that applied the concept of "green hotel" to the hotel building cases that are considered to meet the criteria. As a result, the hotel's green architecture strategy uses a "green" principle that covers aspects of the cultural, social and economic life cycle; structural design efficiency; energy efficiency; water efficiency; efficiency of building materials; improvement of inner space quality; operational and maintenance optimization; and waste reduction.Keywords: design strategy, sustainable architecture, green hotelAbstrak: Penerapan Konsep Pembangunan Berkelanjutan memerlukan integrasi antara skala mikro (bangunan), skala meso (kelompok bangunan) dan skala makro (kota). Sejak tahun 2008, ASEAN telah memberikan penghargaan kepada hotel-hotel di dunia yang memenuhi standar hotel berwawasan lingkungan. Kementrian Pariwisata dan Ekonomi Kreatif mengapresiasi dan menyelenggarakan pemberian penghargaan National Green Hotel Award sejak tahun 2011. Penelitian ini difokuskan pada pengidentifikasian dan analisis strategi-strategi desain berkelanjutan pada tiga hotel di Jakarta dan Bali meliputi upaya efisiensi, konservasi dan pengelolaan berbagai elemen: lahan, energi, air, material, udara dan kesehatan dalam ruang, serta manajemen lingkungan sekitar. Analisis menggunakan pendekatan kritik arsitektur normatif mengenai kajian baku dalam mendesain bangunan hotel yang menerapkan konsep â€œhotel hijauâ€ terhadap kasus-kasus bangunan hotel yang dianggap memenuhi kriteria. Hasilnya, strategi arsitektur hijau pada hotel menggunakan prinsip â€œhijauâ€ yang mencakup aspek-aspek daur hidup budaya, sosial dan ekonomi; efisiensi desain struktur; efisiensi energi; efisiensi air; efisiensi material bangunan; peningkatan kualitas ruang dalam; optimalisasi operasional dan pemeliharaan; dan pengurangan limbah.Kata kunci: strategi desain, arsitektur berkelanjutan, hotel hijau